Social control and the three stages of the control system in contemporary Spain: historiographical orientation - Oliver Olmo, Pedro (Huarte de San Juan. Geografía e Historia, 2025)
This article defines «social control» and the «control system» (police, judicial and penitentiary), to warn about the risks that historical research must face. From this theoretical and methodological basis, the uses (explicit or implicit) of the concept of social control in Spanish historiography are assessed, identifying three stages of the control system: a disciplinary one, which acquired its modern forms with the construction of the Liberal State, reached its climax in the Second Republic and collapsed in the bellicose and repressive dynamics of the Civil War; another punitivist stage, which definitively truncated the evolution of liberal disciplinary control and was developed over the course of the Franco regime, putting the centrality of punishment before the maintenance of political and social order; and a security system, which emerged in the transition from dictatorship to democracy, displaying to the present day the features of the security state and the «society of control».